Factors that determine energy compensation: a systematic review of preload studies. - Almiron-Roig, E; Palla, L; Guest, K; Ricchiuti, C; Vint, N; Jebb, SA; Drewnowski, A (2013)
Insufficient energy compensation after a preload (meal, snack, or beverage) has been associated with excess energy intake, but experimental studies have used heterogeneous methodologies, making energy compensation difficult to predict. The aim of this systematic review was to analyze the relative contributions of two key variables, preload physical form and intermeal interval (IMI), to differences in energy compensation. Forty-eight publications were included, from which percent energy compensation (%EC) data were extracted for 253 interventions (121 liquid, 69 semisolid, 20 solid, and 43 composite preloads). Energy compensation ranged from -370% (overconsumption, mostly of liquids) to 450% (overcompensation). A meta-regression analysis of studies reporting positive energy compensation showed that IMI (as the predominant factor) together with preload physical form and energy contributed significantly to %EC differences, accounting for 50% of the variance, independently from gender and BMI. Energy compensation was maximized when the preload was in semisolid/solid form and the IMI was 30-120 min. These results may assist in the interpretation of studies assessing the relative efficacy of interventions to enhance satiety, including functional foods and weight management products.